“Incorporación de un indicador de accesibilidad de la población en los servicios de salud y educación en el sistema de gestión vial, de la provincia de el oro” - Serrano Ordoñez, Leonardo Francisco (2015)
Road management systems, allowing authorities to distribute financial and material resources, in order to keep roads safe and in good condition; for the population and trade. However rarely involve social elements (1, 2, 3). The province of El Oro, does not have a road management system that will improve the quality of life of people, especially those located in rural areas of it, therefore; the lack of a periodic system of road management can have social and economic impacts on rural communities, and local governments in the province of El Oro (4). A rural road in good condition, ensures better accessibility to markets, schools, health services, and; income and employment opportunities. This plays an important role in supporting rural livelihoods and contribute to poverty alleviation (5, 6, 7). It can be said then that the tracks generate large changes in the territories that circumscribe because they have the best conditions to facilitate mobility. These major changes, while generating economic development, they also bring a problem that threatens the inhabitants of populated areas, and the road system becomes inefficient. With this background, this paper aims to study the rural road system of the Province of El Oro, which based on the territorial objectives. According to the provincial road plan (CAPM, 2003), 9% of roads were in good or very good condition, 13% in fair condition and 78% in poor or very poor condition (4). It should be noted that poor roads and poor alignments, and surfaces in poor condition, preventing timely access to basic health services and education, and damaged products because transport times from the site production to the place of consumption or export lengthen, increased transportation costs and consequently increase the final cost of each and every one of the products produced locally or imported from outside to the local end markets (8) .